A wedding on Primrose Street - Roberts, Sheila, 1951- (Roberts, Sheila, 1951- Life in Icicle Falls, 2015)
"There's nothing like a wedding! The joy, the fun, the memories--the stress. As a wedding planner, Anne Richardson has seen mothers of the bride turn into Momzillas, and she's determined not to do that when it's her daughter's turn to get married. But once Laney gets engaged, all bets are off. Anne becomes obsessed with giving Laney the perfect wedding she herself never had. And that wedding needs to be held in Icicle Falls at Primrose Haus, the perfect setting. Roberta Gilbert, owner of Primrose Haus, has been hosting events at her charming Victorian for thirty years. She's an expert on weddings, but not on mother-daughter relations. When her daughter, Daphne, comes home and decides to help with the business, the reception becomes truly memorable--and not in a good way. Then there's the added complication of Roberta's gardener, who seems more interested in Daphne than he is in planting primroses ... Tying the knot is a business that has everyone tied up in knots!"--